Cytotoxic Effects of Plant Secondary Metabolites and Naturally Occurring Bioactive Peptides on Breast Cancer Model Systems: Molecular Mechanisms - Diana Zasheva; Petko Mladenov; Silvina Zapryanova; Zlatina Gospodinova; Mariyana Georgieva; Irina Alexandar; Valentin Velinov; Dimitar Djilianov; Daniela Moyankova; Lyudmila Simova-Stoilova (Molecules)
Breast cancer is the second leading cause of death among women, and the number of mortal cases in diagnosed patients is constantly increasing. The search for new plant compounds with antitumor effects is very important because of the side effects of conventional therapy and the development of drug resistance in cancer cells. The use of plant substances in medicine has been well known for centuries, but the exact mechanism of their action is far from being elucidated. The molecular mechanisms of cytotoxicity exerted by secondary metabolites and bioactive peptides of plant origin on breast cancer cell lines are the subject of this review.